2012
DOI: 10.1001/archoto.2012.16
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Randomized Controlled Trials Comparing Intracapsular Tonsillectomy With Total Tonsillectomy in a Pediatric Population

Abstract: Recovery-related outcomes for IT were superior to TT (secondary hemorrhage rate, number of days until pain free) in a pediatric population with obstructive symptoms (level-1 evidence).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 31 publications
7
80
1
Order By: Relevance
“…These alternatives might be pharmacological, such as the use of steroidal 18 or nonsteroidal antiinflammatory drugs 19 in addition to acetaminophen, but also surgical, because the use of the intracapsular tonsillectomy technique has been shown to substantially reduce postoperative pain. 20 Finally, this case supports the clinical utility of determining CYP2D6 genotype or phenotype in preventing serious drug adverse effects and developing more individualized analgesic therapy based on therapeutic recommendations according to CYP2D6 genotype.…”
Section: Discussionsupporting
confidence: 55%
“…These alternatives might be pharmacological, such as the use of steroidal 18 or nonsteroidal antiinflammatory drugs 19 in addition to acetaminophen, but also surgical, because the use of the intracapsular tonsillectomy technique has been shown to substantially reduce postoperative pain. 20 Finally, this case supports the clinical utility of determining CYP2D6 genotype or phenotype in preventing serious drug adverse effects and developing more individualized analgesic therapy based on therapeutic recommendations according to CYP2D6 genotype.…”
Section: Discussionsupporting
confidence: 55%
“…According to Walton et al [38] in randomized trials early PTB was present in 3/699 (0.4%) tonsillotomy and 1/635 (0.16%) tonsillectomy patients, a nonsignificant difference. Delayed PTB was found in 5/699 (0.7%) tonsillotomy and 13/635 (2.0%) tonsillectomy patients, a statistically significant difference (p = 0.04).…”
Section: Surgical Technique: How Much Tonsil To Remove?mentioning
confidence: 96%
“…Recently, a meta-analysis of randomized trials [38] and a systemic review, which also included nonrandomized studies [39] , comparing tonsillotomy with traditional tonsillectomy, were published. According to Walton et al [38] in randomized trials early PTB was present in 3/699 (0.4%) tonsillotomy and 1/635 (0.16%) tonsillectomy patients, a nonsignificant difference.…”
Section: Surgical Technique: How Much Tonsil To Remove?mentioning
confidence: 99%
“…Of 16 randomized controlled trials (RCTs) included, the conclusion was that TT was equivalent or superior to TE concerning recovery-related outcomes. 9 However, none of the RCTs reported pre-or postoperative data from polysomnography (PSG), which is the gold standard for diagnosing OSA in children, and for grading the severity. 3 Another review concluded that "large welldesigned randomized controlled trials with an adequate follow-up are necessary to determine whether the procedure (TT) is capable of replacing TE for resolving upperairway obstruction."…”
mentioning
confidence: 99%